2021
DOI: 10.21203/rs.3.rs-513418/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complex Probiotics Supplementation Improves Overtraining-Induced Muscle Inflammatory Response and Antioxidant Status Via LPS-TLR4/NF-κb Signalling Pathway in Rats

Abstract: Background: Prolonged endurance and intensive exercise has shown detrimental effects on muscle health as well as causes intestinal dysbiosis. Probiotics are known as live microorganisms effective in improving gut microbiota and immunity to warrant health and well-being, which exert global and local biological functions on gut and muscle comprising of anti-oxidative stress, anti-inflammatory and anti-apoptosis, etc,. This research was conducted to investigate whether complex probiotics supplementation could all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Cao et al (2021) found that Probio-M8 could alleviate Alzheimer's disease symptoms in APP/ PS1 mice via gut microbiota regulation. Xia et al (2021) found that mixed probiotics (containing Probio-M8) could improve muscle inflammation and antioxidation induced by overtraining through LPS-TLR4/NF-κB signal pathway. Yogurt is a popular drink worldwide, and habitual consumption of yogurt has been found to inversely associate with the prevalence of newly diagnosed nonalcoholic fatty liver disease (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al (2021) found that Probio-M8 could alleviate Alzheimer's disease symptoms in APP/ PS1 mice via gut microbiota regulation. Xia et al (2021) found that mixed probiotics (containing Probio-M8) could improve muscle inflammation and antioxidation induced by overtraining through LPS-TLR4/NF-κB signal pathway. Yogurt is a popular drink worldwide, and habitual consumption of yogurt has been found to inversely associate with the prevalence of newly diagnosed nonalcoholic fatty liver disease (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The strain they used is Bifidobacterium animalis spp. lactis Probio-M8 (Probio-M8), which have showed properties of gut flora modification, anti-inflammation and antioxidant in previous study [30,31]. The results showed rats fed Probio-M8-fermented milk preserved the integrity of their gut microbiota, reduced oxidative stress and hepatic inflammation, and alleviated liver damage.…”
Section: Fermented Milkmentioning
confidence: 98%